The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17582/journal.rjvp/2018/6.3.20.25
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Combinations of Anesthetic Drug on Cardiopulmonary Functions and Recovery Behavior in Horses

Abstract: The objective of this study was to identify the effects of combined anesthetic drugs on heart rate variability (HRV), respiratory function and recovery behavior in horses. Eight healthy Thai native crossbred horses were enrolled in this study. Horses were premedicated and induction with 2 protocols, protocol 1; acepromazine (0.04mg/ kg)+ xylazine (1 mg/kg)+ ketamine (2.2 mg/kg) and protocol 2; detomidine (5 mcg/kg)+ketamine (2.2 mg/kg). Heart rate and heart rate variability of 8horses were measured 20 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…A decrease in LF power in both groups after adrenaline administration indicated vagal inhibition. This study showed that combined drugs in both protocols increased HR and affected parasympathetic activity as a previous study [15]. The higher decrease in HF power in Group 1 indicated a high parasympathetic activity, and horses in this group had high LF/HF ratio values compared with the other group.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A decrease in LF power in both groups after adrenaline administration indicated vagal inhibition. This study showed that combined drugs in both protocols increased HR and affected parasympathetic activity as a previous study [15]. The higher decrease in HF power in Group 1 indicated a high parasympathetic activity, and horses in this group had high LF/HF ratio values compared with the other group.…”
Section: Discussionsupporting
confidence: 83%
“…The echocardiographic examination (Mindray, China) with 2 MHz transducers was done to rule out cardiac pathology and evaluate heart contractility functions. The left ventricular wall structure and function were calculated by measuring the images from a two-dimensional plane as in the previous study [15]. Cardiac parameters such as HR, stroke volume, cardiac output, fractional shortening, and left ventricle internal diameter were evaluated offline.…”
Section: Cardiovascular Variablesmentioning
confidence: 99%
See 2 more Smart Citations